FREQUENCY OF PSYCHIATRIC DISORDERS IN REFERRED HOSPITALIZED PATIENTS OF OTHER MEDICAL DISCIPLINES A HOSPITAL BASED STUDY: Psychiatric Disorders in Referred Patients - Mahar, Surg Lt Cdr Muhammad Ramzan; Jehangir, Salim; Khan, Farrukh Hayat; Arain, Tariq; Jalil, Sadia; ., Fazal-e-Karim (Pakistan Armed Forces Medical Journal, 2010)
Objective: To asses the frequency of psychiatric disorders in the admitted patients of other medical disciplines at PNS Shifa Karachi. Study Design: Cross sectional study. Place and duration of study: The study was conducted at PNS Shifa Karachi from April 2007 to Oct 2007. Patients and Methods: Total of 427 hospitalized patients in other medical disciplines at PNS Shifa Karachi; a tertiary care hospital, referred for psychiatric consultation in sequence were studied. Results: The age of the patients ranged from 13 to 97 years, with the mean age being 43.22 years. Sixty four percent patients of the studied individuals were males. Forty nine percent patients were diagnosed to be suffering from Depression/Dysthymia. Twelve percent patients qualified the diagnosis of Anxiety disorder and Reaction to severe stress and adjustment disorders each. Seventeen percent patients suffered from Dementia, Delirium, Psychoactive substance abuse, Acute & transient Psychotic disorder, Schizophrenia, Bipolar affective disorder/Mood disorder and Puerperal depression. Conclusion: A considerable proportion of psychiatrically ill patients require psychiatric intervention either because of their primary psychiatric disorder or secondary psychological reactions to physical morbidity. Such intervention in time not only improves the quality of patient’s life but also saves the heavy portion of the budget utilized for medical services in these patients later on if not diagnosed earlier.